Several Conventional Risk Markers Suggesting Presence of Albuminuria Are Weak Among Rural Africans With Hypertension. Issue 1 (26th August 2015) - Rasmussen, Jon B.; Nordin, Lovisa S.; Thomsen, Jakúp A.; Rossing, Peter; Bygbjerg, Ib C.; Christensen, Dirk L.
Abstract : The objective of this cross‐sectional study was to investigate risk markers indicating the presence of albuminuria in patients with hypertension in rural sub‐Saharan Africa (SSA). Urine albumin‐creatinine ratio, glycated hemoglobin (HbA1c ), blood pressure, anthropometry, and other patient characteristics including medications were assessed. We identified 160 patients with hypertension, of whom 68 (42.5%) were co‐diagnosed with diabetes mellitus (DM). Among the included participants, 57 (35.6%) had albuminuria (microalbuminuria [n=43] and macroalbuminuria [n=14]). A backward multivariate logistic regression model identified age (per 10‐year increment) (odds ratio [OR], 1.42; 95% confidence interval [CI], 1.03–1.95), HbA1c >53 compared with <48 mmol/mol (OR, 3.81; 95% CI, 1.74–8.35), and treatment with dihydropyridine calcium channel blockers (OR, 2.59; 95% CI, 1.09–6.16) as the variables significantly associated with albuminuria. Only dysregulated DM and age were the conventional risk markers that seemed to suggest albuminuria among patients with hypertension in rural SSA.